Thermo-Economic Comparison Between Organic Rankine Cycle and Binary-Flashing Cycle for Geothermal Energy - Zhao, Yuan; Du, Bowen; Chen, Shunyi; Zhao, Jun; Gong, Yulie; Bu, Xianbiao; Li, Huashan; Wang, Lingbao (Frontiers in Earth Science, 2021)
Geothermal energy is characteristic of widely distributed, high capacity factor, high reliability, and lower environmental impact potential values. And it will play an important role in achieving the goal of carbon neutral carbon peak. Nonetheless, geothermal energy presents its own particular challenges, i.e. the high investment cost and long payback time. The binary flashing cycle (BFC) system is proved to be a promising geothermal power generation technology due to the efficient and fully utilization. The BFC economic performance still need further evaluation. In present study, the thermo-economic comparison between organic Rankine cycle (ORC) and BFC for geothermal energy has been investigated. R245fa has been chosen as the working fluid. Considering the thermodynamic and economic performance, several evaluation indicators were selected including thermal efficiency, exergy efficiency, net power output per ton geothermal water, heat exchanger area and heat recovery efficiency, and the system modeling and comparison were presented. The simulation results reveal that the BFC system sacrifices efficiency, and acquires larger net power output. What is more, the preliminary discussion of the economic feasibility of BFC system applied in FengShun geothermal power plant is presented. The payback period of BFC is just 6.0 years under the generation pressure of 600 kPa. It is indicated that the BFC system has obvious economic benefits, especially in non-flowing geothermal well.